2016
DOI: 10.1002/cbdv.201500158
|View full text |Cite
|
Sign up to set email alerts
|

Novel Nucleolipids of Pyrimidine βD‐Ribonucleosides: Combinatorial Synthesis, Spectroscopic Characterization, and Cytostatic/Cytotoxic Activities

Abstract: Four series of nucleolipids with either uridine, 5-methyluridine, 5-fluorouridine, and 6-azauridine as β-D-ribonucleoside component have been prepared in a combinatorial (not parallel!) manner (see Formulae). All compounds have been characterized by elemental analyses, ESI mass spectrometry as well as by (1) H-, and (13) C-NMR, and UV spectroscopy. A selection of eight nucleolipids with different lipophilizing moieties, based on earlier findings, as well as of 5-fluorouridine as control were first tested on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…We also showed that saponification of the O ‐2′,3′‐ethyl levulinate ketal group yielding an O ‐2′,3′‐levulinate residue at the glyconic moiety of the ribonucleoside abolishes any cancerostatic/cancerotoxic activity toward human cancer cell lines . We extended our study to canonical purine β ‐ d ‐ribonucleoside nucleolipids, particularly to inosine and adenosine derivatives …”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…We also showed that saponification of the O ‐2′,3′‐ethyl levulinate ketal group yielding an O ‐2′,3′‐levulinate residue at the glyconic moiety of the ribonucleoside abolishes any cancerostatic/cancerotoxic activity toward human cancer cell lines . We extended our study to canonical purine β ‐ d ‐ribonucleoside nucleolipids, particularly to inosine and adenosine derivatives …”
Section: Introductionmentioning
confidence: 66%
“…Reaction of the pyrimidine β ‐ d ‐ribonucleosides 1Aa – 1Ad and the purine β ‐ d ‐ribonucleosides 1Ba and 1Bb with either heptan‐4‐one or undecan‐6‐one gave after chromatographic work‐up the symmetric O‐2′,3′‐ketals 2Aa – 2Ah and 2Ba – 2Bd ( Scheme 1 ). Some of these nucleolipids had already been prepared before and were now re‐synthesized. For comparison, adenosine was ketalized with cyclopentadecanone yielding the O‐2′,3′‐cyclic cyclopentadecanylidene nucleolipid 4 ( Scheme 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…36 Of course, modication of the nucleic base might negate (or at least dramatically decrease) the possible recognition with complementary nucleosides; however, it might allow nucleoside selfassemblies, as observed in nucleolipids. 37,38 As mentioned, the nucleoside and EDOT parts were linked using nucleophilic substitution. It was thus necessary to prepare EDOT bearing a good leaving group (Br).…”
Section: Synthesismentioning
confidence: 99%